Altered Brain Activity and Effective Connectivity within the Nonsensory Cortex during Stimulation of a Latent Myofascial Trigger Point - Xinglou Li; Meiling Luo; Yan Gong; Ning Xu; Congcong Huo; Hui Xie; Shouwei Yue; Zengyong Li; Yonghui Wang (Neural Plasticity)
Myofascial trigger point (MTrP), an iconic characteristic of myofascial pain syndrome (MPS), can induce cerebral cortex changes including altered cortical excitability and connectivity. The corresponding characteristically reactive cortex is still ambiguous. Seventeen participants with latent MTrPs underwent functional near-infrared spectroscopy (fNIRS) to collect cerebral oxygenation hemoglobin (Δ[oxy-Hb]) signals. The Δ[oxy-Hb] signals of the left/right prefrontal cortex (L/R PFC), left/right motor cortex (L/R MC), and left/right occipital lobe (L/R OL) of the subjects were measured using functional near-infrared spectroscopy (fNIRS) in the resting state, nonmyofascial trigger point (NMTrP), state and MTrP state. The data investigated the latent MTrP-induced changes in brain activity and effective connectivity (EC) within the nonsensory cortex. The parameter wavelet amplitude (WA) was used to describe cortical activation, EC to show brain network connectivity, and main coupling direction (mCD) to exhibit the dominant connectivity direction in different frequency bands. An increasing trend of WA and a decreasing trend of EC values were observed in the PFC. The interregional mCD was primarily shifted from a unidirectional to bidirectional connection, especially from PFC to MC or OL, when responding to manual stimulation during the MTrP state compared with resting state and NMTrP state in the intervals III, IV, and V. This study demonstrates that the nonsensory cortex PFC, MC, and OL can participate in the cortical reactions induced by stimulation of a latent MTrP. Additionally, the PFC shows nonnegligible higher activation and weakened regulation than other brain regions. Thus, the PFC may be responsible for the central cortical regulation of a latent MTrP. This trial is registered with ChiCTR2100048433.